School gardens and biofertilization as a strategy towards climate change mitigation and adaptation in Costa Rica = Huertas escolares y biofertilización como estrategia hacia la mitigación y adaptación al cambio climático en Costa Rica - Rojas Alvarado, Carlos Alonso 1976-
School gardens are important for the conceptual integration of topics such as climate change. Using a biofertilization experiment in a school garden, we evaluated four experimental treatments and the student knowledge to some sustainable practices. Solid bio-fertilization was more effective than liquid treatments. The effect of the garden establishment was positive on the knowledge demonstrated by students. Similar activities are recommend-ed in the context of primary education in Costa Rica.